Mechanical modeling of plantar pressure during human walking in different terrains: Experiments and analysis - Liu, Jiaqi; Fang, Hongbin; Feng, Mingfei; Zhang, Qiwei; Xu, Jian (European journal of mechanics, A, Solids, 2025)
Accurate plantar pressure models play a pivotal in predicting human gait dynamics and have broad applications, including the development of exoskeletons, prosthetics, and legged robots. However, existing models often overlook the influence of varying terrains on plantar pressures. In this study, we conducted a comprehensive modeling analysis of plantar pressure using experimental walking data collected from 12 subjects (6 males and 6 females). Statistical analysis reveals significant variations in vertical ground reaction forces across different plantar regions and terrains. In response to these findings, we develop a novel viscoelastic ellipsoid model capable of describing the complex mechanical behavior of foot-ground contact. The plantar tissue is divided into five distinct regions, each represented by an ellipsoid with viscoelastic material properties. Our model also expresses the plantar deformation by the contact area, which can be measured by in-shoe pressure sensors, thus addressing the challenge of measuring plantar tissue deformation in walking experiments. Additionally, we employ a quasi-static contact model to estimate the equivalent contact area, overcoming the challenge of contact area saturation during walking and improving the model's accuracy. Based on this foundation, we apply an intelligent optimization algorithm to identify the optimal geometric and material parameters of the ellipsoid models. Comparison of model outputs and experimental results demonstrate that the ellipsoid model can accurately render the vertical ground reaction forces of different plantar regions under various terrains, providing valuable insights into foot-ground interaction. Moreover, by comparing the results of parameter optimization in different terrain contexts, we unveil the critical relationships between terrain factors and model parameters, thereby deepening our understanding of foot-ground contact mechanics. •Experiments reveal significant variations in VGRF in different plantar regions and terrains.•A viscoelastic ellipsoid model incorporating five distinct plantar regions is developed.•Equivalent contact area is estimated to solve contact area saturation and improve accuracy.•Comparison of predictions and test results indicate high accuracy and robustness of model.•Critical relationships between terrain factors and model parameters are unveiled.